Social Inclusion of Gen Z Ukrainian Refugees in Lithuania: The Role of Online Social Networks - Isabel Palomo-Domínguez; Jolanta Pivorienė; Odeta Merfeldaitė (Social Sciences, 2024)
Since the start of the war in Ukraine, Lithuania, a country of barely 3 million inhabitants, has welcomed more than 85,000 refugees, mainly minors and young people. This research focuses on the youth segment, members of Gen Z, which exhibits a marked gender bias, as the majority are women. The purpose of this study is to determine the role played by online social networks in the process of social inclusion in the host community. Methodologically, this research conducts a qualitative approach through in-depth interviews with open code content analysis. The results point to changes in their behavior as social media users, such as using new online social networks, and greater attention to practical topics such as knowing necessary services and leisure opportunities in their new environment. Among the conclusions, the positive effect of online social networks in the social inclusion process of these young refugees stands out: being members of the local virtual community facilitates new social interactions in the physical world of the host country.